Prevalence of Lung Cancer in Al Najaf Governorate Registered in Middle Euphrates Oncology Center during 2019 and 2020 - Al-Khateeb, Zahraa; Mahdi, Liwaa (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Lung cancer is a disease in which cells in the lung grow out of control and may spread to lymph nodes or other organs in the body such as the brain. Cancer from other organs also may spread to the lungs. The chance that a man will develop lung cancer in his lifetime is about 1 in 15; for a woman, the risk is about 1 in 17. These numbers include both people who smoke and those who don’t smoke. Worldwide; prevalence of the lung cancer was decreased in the last decade. Objectives: To determine the prevalence of lung cancer in Al Nagaf Governorate during 2019 and 2020 Patients and Methods: A Registry-based cross sectional study was conducted at middle Euphrates oncology center in Al Najaf city from October 2021 to February 2022. data was collected from this center and from the Iraqi National Cancer Registry (INCR) annual reports. Independent t test (Mean±SD) and X2 test was used, P value at < 0.05 was significant. Results: In 2019; there were 98 (53.60%) patients diagnosed with lung CA, while in 2020, there were 85 (46.40%) patients. 59 (32.20%) patients were within age 60-69 years and 59 (32.20%) patients were within age 70-79 years. There were 125 (68.3%) males and 58 (31.7%) females, 138 (75.40%) smokers, and 59 (32.20%) patients were overweight. 103 (56.3%) patients diagnosed with SCC, 43 (23.5%) with adenocarcinoma, 32 (17.5%) with small cell CA. Cancer metastasis found among 108 (59%) patients. bone in 35 (19.1%) patients and to the Liver in 30 (16.4%) patients. Prevalence of Lung CA in 2019 was 6.5/105 (in males 8.72/105 and 4.25/105 in females). During 2020; there were 59 males and 26 females. Prevalence of Lung CA was 5.5/105 (in males 6.7/105 and 3.4/105 in females). Small cell CA was significantly associated with patients aged 60-69 years, smokers, diagnosis with biopsy, metastasis to the supraclavicular LN, and metastasis to the liver (P<0.05). Conclusions: Prevalence of lung CA in 2019 was higher than that in 2020. Males were dominant in lung CA. Metastasis was found among more than half of patients; bone and liver were the most common metastasized organs. The most common types of cancer were Squamous Cell CA, adenocarcinoma, and Small Cell CA.